2020
DOI: 10.26434/chemrxiv.12599915
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In Silico Screening of Phytochemicals of Ocimum Sanctum Against Main Protease of SARS-CoV-2

Abstract: <div>COVID19 has compelled the scientific community to search for an effective drug that can cure; a vaccine or an immunity booster that can prevent the disease. As of now, it is tough to discover a new drug and vaccine discovery is even tougher. Drug repurposing is a shortcut to drug discovery for COVID19. Even this has been proved unsatisfactory. Symptomatic treatment and immunity boosters are only alternatives left. Holy Tulsi (Ocimum sanctum) has been known as an ancient remedy for cure of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…As a result, chlorogenic acid and luteolin-7-O-glucuronide emerge as the most promising candidates. Chlorogenic acid is mostly found in coffee beans, although it is also found in tea leaves [56] . Varshney and colleagues reported that Dihydrodieuginol B and Tulsinol A, B, C, D, E, F, G from O. sanctum can be utilised as possible inhibitors for papain-like Protease (PL pro ) and SARS COV-2 Main Protease [57] ( Fig.…”
Section: Natural Products As Medicines For Covid-19mentioning
confidence: 99%
“…As a result, chlorogenic acid and luteolin-7-O-glucuronide emerge as the most promising candidates. Chlorogenic acid is mostly found in coffee beans, although it is also found in tea leaves [56] . Varshney and colleagues reported that Dihydrodieuginol B and Tulsinol A, B, C, D, E, F, G from O. sanctum can be utilised as possible inhibitors for papain-like Protease (PL pro ) and SARS COV-2 Main Protease [57] ( Fig.…”
Section: Natural Products As Medicines For Covid-19mentioning
confidence: 99%
“…The antiviral capacity of ethanolic and aqueous extracts of O. sanctum was examined by infecting Madin-Darby Canine Kidney (MDCK) cells with the H1N1 virus and subsequently treating them with ethanolic and aqueous extracts of O. sanctum ; the ethanolic extract demonstrated strong antiviral activity against H1N1 at 150 µg/mL [ 59 ]. In silico analysis showed that luteolin-7-O-glucuronide and chlorogenic acid present in O. sanctum could covalently bind to Cys145 of M pro of SARS-CoV-2 and may hinder the viral enzymes [ 60 ].…”
Section: Plants Of Indian Origin and Common Usementioning
confidence: 99%
“…In silico analysis showed the binding of phytochemical orientin to the Glucose Regulating Protein 78 (GRP78 protein), an important region where virus can bind to gain entry into the host (Bhowmik et al 2021). In another report, bioinformatics studies revealed that flavonoid luteolin-7-O-glucuronide and polyphenolic chlorogenic acid binds with the Cys145 of viral protease and can permanently inhibit its activity (Mohapatra et al 2020).…”
Section: Plants With Immunomodulatory and Antiviral Potentialmentioning
confidence: 99%